IMPLEMENTASI "GROUP-INVESTIGATION COOPERATIVE" BERORIENTASI KONTEKSTUAL DI SMPN 2 TAMAN SIDOARJO DALAM PEMBELAJARAN SAINS-KIMIA - Harun Nasrudin, ; Utiya Azizah, (Jurnal Penelitian Pendidikan Matematika dan Sains, 2008)
Abstract:  To increase the quality of teaching-learning in science, contextual oriented using  Group-Investigation Cooperative was implemented. A classroom action research in three cycles has been done to know the effectiveness of science learning using contextual oriented. Students who were studying science at Junior High School seventh Year Student in 2007/2008 year. There are some important points can be drawn from the result of analysis: Implementation of group investigation Cooperative contextual oriented in science (1) can be done by teacher well and relevant with models syntax was implemented; (2) can improve students activeness in learning science, as indicated by discussion within students, doing investigation (theory/observation/experiment), teachers-students discussion, presentation of final product, and volunteer (student express their opinion and responses); (3) can improve students activeness in learning science, as indicated by the students achievement mastery for first cycle is 43,6%, the second cycle is 61,5%, and the third cycle is 74,4%; and (4) Most of students are wilingly to joint to this teaching-learning activity, and the improvement of students cooperate in esential concepts finding so learning not boring. Students can be done analysis and evaluation investigation result with their ideas, observation environment theirself, make report investigation and presentation of final product.